A new species in the genus Alopecosa Simon, 1885 from Korea (Araneae: Lycosidae) - Yoo, Jungsun; Kim, Joopil; Tanaka, Hozumi (Zootaxa, 2004)
Alopecosa volubilis n. sp. is described from Korea and is differentiated from other species in Alopecosa Simon, 1885 by morphological characteristics, such as three retromarginal teeth of chelicera, smaller body size, and the presence of a distinct tip of the median apophysis. The pedipalpal sclerites and somatic characters of two similar species, A. moriutii Tanaka, 1985 and A. hokkaidensis Tanaka, 1985, are compared with those of the new species. An illustration of the body and scanning electron microscope (SEM) pictures of the pedipalpal organ are provided.